2010
DOI: 10.1016/j.ijgo.2010.07.024
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnetic resonance imaging in fetal renal anomalies

Abstract: Ultrasound is the imaging modality of choice for the diagnosis of fetal renal anomalies; fetal MRI is a useful adjunct, especially when ultrasound is inconclusive owing to oligohydramnios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…However, postnatal kidney function is difficult to predict based on ultrasound studies, especially the long-term outcome [4,5]. Magnetic resonance imaging scans can provide additional information on fetal urinary tract abnormalities in some cases, but these have not been evaluated as a modality to predict postnatal outcome [6,7]. Therefore, some studies have focused on the assessment of biochemical markers in fetal urine or blood to predict the postnatal outcome of kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…However, postnatal kidney function is difficult to predict based on ultrasound studies, especially the long-term outcome [4,5]. Magnetic resonance imaging scans can provide additional information on fetal urinary tract abnormalities in some cases, but these have not been evaluated as a modality to predict postnatal outcome [6,7]. Therefore, some studies have focused on the assessment of biochemical markers in fetal urine or blood to predict the postnatal outcome of kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al conducted a prospective study in which they performed MRI studies of fetuses with suspected renal abnormalities based on sonographic examination. These authors reported that MRI results confirmed ultrasound findings in 70.4 % of fetuses and supplied additional information in 25.9 % [20]. Especially in fetuses with ROH, MRI may therefore provide more specific information that can be important for postnatal management and prognosis.…”
Section: Antenatal Imaging Of the Fetal Urogenital Tract And Lungsmentioning
confidence: 80%
“…Single renal cyst -----3 -3 Megacystis -1 ----2 3 + hydroureter Total 1 17 18 9 2 3 2 52 populations, is about 0.1 to 0.7% (16) Twenty-seven fetuses with suspected renal anomalies on ultrasound (study group) were rescanned by MRI by Gupta et al (10) and they found that a total of 10 (37%) cases were associated with severe oligohydramnios (10). It was reported that unilateral hydronephrosis is the most common fetal renal anomaly and normal amniotic fluid volume is the usual finding, but oligohydramnios is associated with bilateral renal anomalies (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Fetal MRI was introduced in 1983, but the ultra-fast MRI sequences allows excellent detection of fetal anatomy without the need for maternal sedation (7)(8)(9). MRI as a complementary modality is more popular in such a setting because it enables the fetus to be viewed in multiple planes, irrespective of fetal lie and has excellent resolution (10,11). This study was designed to detect the role of magnetic resonance imaging in refining the diagnosis of suspected fetal renal anomalies detected during screening sonography.…”
Section: Introductionmentioning
confidence: 99%